KAJIAN DAYA DUKUNG LINGKUNGAN PERMUKIMAN DI KECAMATAN UMBULHARJO YOGYAKARTA - , Rinaningtyas Anggriani Putri, Dr. Luthfi Mutaâali, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The construction of settlement in Umbulharjo Subdistrict occurs rapidly without being balanced by increasing the basic service facilities. This settlement development causes the increase in building density (building densification). The building density pressures the residential land and is feared to exceed the carrying capacity. The research objectives are: (1) to identify the distribution pattern of settlements in Umbulharjo subdistrict